Short communication: Endophytic actinobacteria isolated from ginger (Zingiber officinale) and its potential as a pancreatic lipase inhibitor and its toxicity - SRI RAHAYU; LENNI FITRI; YULIA SARI ISMAIL (Society for Indonesian Biodiversity, 2019)
Abstract. Rahayu S, Fitri L, Ismail YS. 2019. Short communication: Endophytic actinobacteria isolated from ginger (Zingiber officinale) and its potential as a pancreatic lipase inhibitor and its toxicity. Biodiversitas 20: 1312-1317.  Endophytic actinobacteria from ginger (Zingiber officinale Rosc.) is a bacterium that is capable of producing secondary metabolites that are the same as their hosts. This study aims to look at the potential of endophytic actinobacteria from ginger as a pancreatic lipase inhibitor and its toxicity. Endophytic actinobacteria were isolated, purified, then tested for pancreatic lipase inhibitors and their toxicity using the BSLT method (Brine Shrimp Lethality Test) and phytochemical tested on ethanol extract of selected isolates. Seven endophytic actinobacterial isolates were isolated from the ginger rhizome. The isolates had different morphological diversity based on colony and microscopic observations and 5 isolates had pancreatic lipase inhibitor activity. The highest inhibitors were found in AJ4 isolates (89.9%), compared with pancreatic lipase inhibitors crude extracts of ginger (68.9%) and orlistat (88.1%) as positive controls. The LC50 value of AJ4 isolates was 653,381 ppm and the value of LT50 was 17,569 hours. AJ4 isolates contain terpenoids, phenols, tannins, flavonoids, alkaloids, and saponins. This research data is considered as new information about the potential of endophytic actinobacteria from ginger as pancreatic lipase inhibitors and their toxicity.